Balai-tulay utilizing habitable bridges as a new paradigm for public housing - Ponce, Josef Mari N. (College of Architecture, University of the Philippines Diliman, 2014)
Balai-Tulay is an exploratory that seeks to address alternative concepts in approaching public housing in the country. The project primarily integrated a housing facility with a bridge structure as a bold statement for on-site relocation in the context. By combining the two structures, the project explores the new dwelling culture a habitable bridge has to offer. Various Filipino values has been integral in the course of the study to conceptualize the problems to the specific needs of the Filipino household. The project focused on a specific housing tenement in Santa Ana , Manila named Punta that are in danger of relocation because the housing facility is already structurally unstable. Aside from that, the tenement is perched on a high-risk flood zone. In addition, the tenement housing is also isolated from the Santa Ana area. Thus, the habitable bridge must be tailored correctly to address these problems in the design. The study also seeks to contribute to a body of knowledge on how air rights development can be utilized in the country. The concept has yet to be explored in the infrastructural landscape of the country in order to serve as a substitute for land development. Moreover, the study can springboard researches on air rights development that could streamline guidelines appropriate to our context.